Ultra-precision grinding of PZT ceramics--Surface integrity control and tooling design - Arai, S.; Wilson, Stephen A.; Corbett, John; Whatmore, Roger W. (Elsevier, 2009)
A comprehensive statistical analysis of the factors controlling surface quality and form in ultra-precision grinding of polycrystalline lead zirconate titanate (PZT) ceramics has been conducted. The work focuses on practical grinding conditions and it includes an assessment of the interactions that exist between the method of material removal and the machine design. In the first phase of experimentation, defects including porosity and the fractural damage induced in the subsurface area were investigated. Machining trials were then conducted which were used to highlight the significant technical factors or combinations of technical factors that influence surface roughness, surface flatness and textural damage. A model for the systematic material removal mechanism which suggests that a relatively large depth of cut and ‘soft contact’ can be used to achieve improved surface integrity is proposed. In order to verify the suggested model, a series of design modifications to the tooling structure were made and the nature of the contact at the material removal interface was studied. Dramatic improvements in surface quality were achieved by incorporating a compliant polymer layer into the vacuum chuck used to hold the ceramics during grinding.
Keywords: Micro-actuator; Piezoelectric; Soft contact; Force path; Acceptance; MEMS